Studi Komparatif Fungsionalitas, Performance dan User experience pada Website Geopark - Bambang Wisnuadhi; Asri Maspupah; Sri Ratna Wulan; Muhammad Rizqi Sholahuddin; Siti Dwi Setiarini; Lukmannul Hakim Firdaus (Journal of Information System Research (JOSH), 2022)
Indonesia has great natural resources. UNESCO recognized at least six geoparks, and Indonesia will continue to develop more geoparks in the future. However, currently, Indonesia's geoparks are not widely known. One of the reasons is that the existing websites do not pay attention to performance guidelines, information, economics, and search engine optimization even though the website is a vital marketing medium so that geoparks can be promoted widely and effectively. A comprehensive study of the website contents is required to build a good geopark website. In addition, it is also necessary to study user experience when visiting web pages. This study aims to find the standard website content on the geopark website and compare existing website performance and user experience. This study compares three geopark websites. The three websites include the Ciletuh-Palabuhanratu, Hongkong geopark, and Cliff of Fundy Geosite website. Three indicators are used: website performance, user experience, and what information should be on the geopark website. These three indicators are essential as an attraction for website visitors so they can enjoy the content of the website and they can stay longer so that the visitors can turn into potential geopark tourists. Good website performance is supported by consistent ease of providing information and speed in providing information to website visitors. In comparison, the user experience visiting the website relates to the interactive visual design, organization, and navigation structure of the website framework and the completeness of the content. We use performance and user experience metrics as evaluation tools for the three selected websites. As a result, the general availability of information is as follows: information about geoparks, UNESCO, list of tourist attractions, activities, itinerary, tourist accommodation, education, contacts, language choices, news articles, pamphlets, maps, and virtual tours. In terms of performance, the three websites have slow speeds, but in cumulative layout shifts, they have good scores.